Evaluation of salivary osteocalcin level in smokers and non-smokers with dental implants: research article - Fakhrzadeh, V.; Eslami, H.; Farhadi Shabestari, F.; Zohdi, M.; Hasanalizadeh, B.; Yasamineh, N. (Journal of Osseointegration, 2022)
Aim The present study is designed to evaluate the salivary osteocalcin level of smokers and peer non-smokers to better understand the mechanisms involved in the effects of smoking on dental implants. Methods The present clinical trial was conducted on saliva samples of patients with dental implants referring to the dentistry faculty of Tabriz University of Medical Sciences. Based on study inclusion and exclusion criteria, eligible patients were divided into two groups of smokers (case group) and non-smokers (control group), each including 35 patients. ELISA (enzyme-linked immune sorbent assay) kit was used to measure the salivary osteocalcin level. Results were analyzed using descriptive statistical methods (mean±SD, frequency, percentage) and SPSS version 17.Results The salivary osteocalcin level is significantly lower in smokers compared with nonsmokers. Conclusion Lower salivary osteocalcin level in smokers compared to nonsmokers may relate to bone resorption and high rate of dental implant failures in smokers